Effect of NPK on growth, yield and seed quality of hybrid Chilli (International Journal of Agricultural Research, Innovation and Technology, 2019)
An experiment was carried out at Germplasm Centre and Plant Biotechnology Lab, Department of Horticulture, PSTU to evaluate the growth, seed yield and quality of hybrid F1 chilli (cv. Sonic) crossing male line (LTSL-004-M) and female line (LTSL-004-F) along the viability of productive seeds influenced by NPK fertilizers during the period from November 2015 to October 2016. Ten different treatments of NPK fertilizers were used. Result showed that all the characteristics except primary branches and1000 seed weight were influenced significantly due to the application of NPK fertilizers. The tallest plant (69.88 cm), more leaves plant–1 (2491.33), highest number of secondary branches plant-1, tertiary branches plant-1 (5.00 and 88.00, respectively), number of flowers and hybrid fruits plant–1 (1533.00 and 12.33, respectively) and weight of seeds (4.03 g plant–1) along with required more time (54.67 days) for flowering were obtained from the application of 145 kg N ha–1, 175 kg P ha–1 and 96 kg K ha–1 (T4) which produced the highest final seed yield of chilli (4.03 kg ha–1). Application of T5 and T9 showed the highest number of primary branches (2.33). In seed viability characteristics T9 treated seeds showed the highest germination (100, 97.33 and 94.97%) at 1st, (1 MAH - Month After Harvest), 2nd (2 MAH) and 3rd (4 MAH) observations, respectively. The T3 treated seeds performed well in respect of Seed Vigour Index (SVI) at 1st and 2nd observations (8.00 and 7.48, respectively) but T9 treated seeds showed the highest SVI (6.32) at 3rd observation. Above indicating all characteristics were lowest under only recommended doses of NPK T1 as control treatment except days to first flowering. The observations suggested that production of hybrid chilli seeds could be enhanced by applying T4. While seeds of chilli treated by T9 in field level showed long time viable. Application of 145 kg N ha–1, 175 kg P ha–1 and 96 kg K ha–1 may be suggested for seed production of chilli and 110 kg N ha–1, + 175 kg P ha–1 + 115 kg K ha–1 for keeping the long time seed viability.Int. J. Agril. Res. Innov. & Tech. 9 (1): 35-41, June, 2019